Conservação, salvaguarda e valorização do património arquitectónico : Mosteiro Santa Maria das Júnias - Pereira, Eva Alexandra (2017)
The heritage and its subsequent recovery as well as conservation, obtained throughout the ages a growing importance. In such a way that recovery or conservation and of a possible, and national classification by IGESPAR, and international, by UNESCO have been again recovered, rediscovered and giving them uses, directly or indirectly, as is the case under study in this dissertation. The monastery of Santa Maria das Júnias is integrated in the National Park of Peneda Gerês and is a monastery in sorne state of disrepair. The conservation and valorization of the monastery, focused on introducing and pathways, with the proposed deployrnent of an Interpretive Centre that will explain, as well as, the overvaluation of the adjacent landscape and emerging pathways that will give a new role to the already very visited and traversed rnonastery, as well as the waterfall located near and on the follow-up to the courses already delineated.